Microwave-assisted metal-ion attachment for ex-situ zirconium doping into hematite for enhanced photoelectrochemical water splitting. (April 2022) - Dhandole, Love Kumar; Anushkkaran, Periyasamy; Hwang, Jun Beom; Chae, Weon-Sik; Kumar, Manish; Lee, Hyun-Hwi; Choi, Sun Hee; Jang, Jum Suk; Lee, Jae Sung
Abstract: Ex-situ doping into hematite films is carried out via a short-duration (∼60 s) microwave-assisted metal-ions attachment (MWMA) of tetravalent Zr 4+ ion on the surface of FeOOH/FTO, followed by high temperature annealing (HTA) to fabricate Zr 4+ :Fe2 O3 /FTO photoanode for photoelectrochemical (PEC) water splitting. Compared to a simple dipping attachment without microwave irradiation, this MWMA allows a much larger amount of attached Zr 4+ -ions on the FeOOH precursor, leading to a properly doped photoanode of much higher PEC activity. The primary effect of Zr 4+ doping is to improve the charge transport characteristics in the bulk of hematite. In addition, it also boosts charge injection efficiency at the semiconductor and electrolyte interface by forming an inadvertent passivation layer and promoting hole transfer via surface states. As a result, the Zr 4+ :Fe2 O3 /FTO photoanode shows a higher photocurrent density of 1.54 mA cm −2 at 1.23 VRHE under 1 Sun irradiation relative to undoped Fe2 O3 /FTO (1.02 mA cm −2 ) or Zr 4+ :Fe2 O3 /FTO (1.19 mA cm −2 ) prepared without MWMA. Graphical abstract: Microwave irradiation energized the suspended Zr 4+ ions to give a higher coverage on the FeOOH film for effective doping of hematite photoanode. The Zr-doping improves not only bulk charge transport properties, but also boosts charge injection performance at the semiconductor-electrolyte interface by forming an inadvertent passivation layer and promoting hole transfer via surface states. Image 1